Vodafone : the Importance of Dynamic Capabilities in an Innovative Market - Peres, Tiago Luís Boto (2019)
The Global Telecommunications Market is probably the most competitive industry worldwide. In the market of the Telecommunications Operators (TelCo’s) everything occurs at a vertiginous speed, making use of the most innovative technologies, implemented in a planetary scale. I trusted that it could be the ideal scenario for my dissertation, whose aim is analysing Competitive Advantage Theories and learning how a market leader does to keep growing and be the most innovator player. The challenges faced by the Global Market will be addressed, in the form of a case study, focusing specifically on Vodafone, one of the largest Telco’s, worldwide, and analysing evidence of how it ensures its competitiveness in the present and projects the future. It is intended that this case study can be used as a teaching tool, providing practical clues from a concrete example, to analyse the strategic structures, their general principles and applicable theories. The case focuses on the analysis of resources and capabilities, taking into account external shocks and internal changes. With the analysis of this case study, I intend to identify evidences that could help to answer to the research question: “What are the unique resources and capabilities that Vodafone possesses that constitute its competitive advantage and in what way did they’ve been developed”.